Аналіз правового реагування працівників поліції на випадки домашнього насильства під час військової агресії в Україні - Макарова, О. П.; Makarova, O. P.; Зінченко, Д. А.; Zinchenko, D. A. (Габітус. - 2023. - Вип. 49. - С. 199-203, 2023)
Проведено теоретичний аналіз нормативно-правового законодавства України щодо випадків та реагування на домашнє насильство. Розглянуто соціально-психологічні та культурні аспекти проблеми домашнього насильства, які мають великий вплив на результативність реагування поліції на це явище. Під час військових дій домашнє насильство дещо трансформувалося та загострилося. Особливо складним є реагування працівників поліції на випадки домашнього насильства, які скоються на окупованих територіях або на територіях, де відбуваються активні бойові дії. Національна поліція України адаптується до механізмів реагування на правопорушення у сфері домашнього насильства під час війни. Резюмовано, що протидія домашньому насильству потребує конкретних дій і з боку постраждалої особи. Аналіз правового реагування на випадки домашнього насильства дав змогу виділити перелік органів та установ, на які покладаються функції зі здійснення заходів у сфері запобігання та протидії домашньому насильству. Відзначено, що навіть під час дії військового стану постраждалі від домашнього насильства можуть стати на свій захист та розірвати насильницьке коло.

The proposed article analyzes the legal response to cases of domestic violence by police officers during military aggression in Ukraine, which is an important issue and requires careful theoretical research. Normative legal acts on the prevention and counteraction of domestic violence are outlined, namely the Laws of Ukraine «On Amendments to the Code of Ukraine on Administrative Offenses Regarding Establishing Responsibility for Committing Violence in the Family or Failure to Fulfill a Protective Order», «On Prevention and Counteraction to Domestic Violence», «On making changes to the Criminal and Criminal Procedure Codes of Ukraine in order to implement the provisions of the Council of Europe Convention on the Prevention of Domestic Violence and the Fight against this phenomenon». The theoretical analysis of normative legal legislation of Ukraine regarding cases and response to domestic violence is defined. In addition, the theoretical analysis of the study examines the socio-psychological and cultural aspects of the problem of domestic violence, which have agr eat impact on the effectiveness of the police response to this phenomenon. The results of this study can become the basis for further improvement of the legislation and practice of combating domestic violence in the context of military aggression in Ukraine. The research determines the need for a scientific analysis of legal frameworks for combating domestic violence. It is noted that the military actions on the territory of Ukraine have reduced interest in covering the issue of domestic violence in the information space. The war makes its corrections in social life and in the life of every person. Today, the power structures of Ukraine must not only repel the enemy, but also take care of the rights of every citizen and carefully monitor that their rights are not violated. Now every Ukrainian is under constant stress and fear, so their reaction to current events is different. And unfortunately, people are beginning to show aggressive actions towards their relatives and friends, so the level of violence in the family is increasing. During the hostilities, domestic violence was somewhat transformed and intensified. It is especially difficult for police officers to respond to cases of domestic violence that occur in occupied territories or in territories where active hostilities are taking place. The National Police of Ukraine is adapting mechanisms for responding to offenses in the field of domestic violence during the war in Ukraine. It is summarized that combating domestic violence requires specific actions on the part of the victim. Therefore, the analysis of the legal response to cases of domestic violence made it possible to identify a list of bodies and institutions entrusted with the functions of implementing measures in the field of prevention and counteraction of domestic violence. Therefore, even during martial law, victims of domestic violence can stand up for themselves and break the cycle of violence.

Проведен теоретический анализ нормативно-правового законодательства Украины относительно случаев и реагирования на домашнее насилие. Рассмотрены социально-психологические и культурные аспекты проблемы домашнего насилия, которые оказывают большое влияние на результативность реагирования полиции на это явление. Национальная полиция Украины адаптируется к механизмам реагирования на правонарушения в сфере домашнего насилия во время войны. Резюмировано, что противодействие домашнему насилию требует конкретных действий и со стороны пострадавшего. Отмечено, что даже во время действия военного положения пострадавшие от домашнего насилия могут стать на свою защиту и разорвать насильственный круг.
Analysis of the normative and legal response of police officers to cases of domestic abuse during military aggression
Keywords: домашнє насильство; domestic violence; домашнее насилие; працівники поліції; police officers; работники полиции; протидія домашньому насильству; combating domestic violence; противодействие домашнему насилию; правове регулювання; legal regulation; правовое регулирование; постраждала особа; injured person; пострадавшее лицо; воєнний стан; martial law; военное положение